Penerapan Edukasi Tentang Protokol Kesehatan Terhadap Pengetahuan dan Sikap Masa Endemi Covid-19 Anak Usia Sekolah - Yunika Puspita Sari; Andi Arniyanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Coronavirus disease can be transmitted caused by the severe acute respiratory syndrome coronavirus 2 (SARS-Cov 2) Virus. Children's health degree cannot be said to be good because there are still health problems, especially in school-age children. Method: Quantitative research with a descriptive approach. Results: Showed good knowledge and positive attitude 88%; there was an increase in knowledge and attitude during the education aftermath. Conclusion: After education on health protocols, there was an increase in knowledge and attitudes in school-aged children during the endemic period of COVID-19. Implementing health protocols correctly and appropriately inside and outside the school environment can prevent the transmission of covid-19